The effect of Nozevit on leucine aminopeptidase and esterase activity in the midgut of honey bees (Apis mellifera) - I. Tlak Gajger; S. Nejedli; Z. Kozaric (Veterinární Medicína, 2013)
The histochemical activity of aminopeptidase and non-specific esterase, both important enzymes of intermediate metabolism in the mid gut of honeybees (Apis mellifera), was investigated. Nosema disease control poses a major challenge, and thus, the treatment of this serious parasitic disease using natural phyto-pharmacological preparations could be of great besnefit. Additionally, the effects of residues and their by-products in honey and wax represent an environmental concern and are another reason for reducing the use of conventional chemical control methods in beekeeping. Nozevit is a naturally prepared water solution of plant polyphenols, and is distributed throughout the market as "the partner for Nosema disease repression". Samples of the midgut tissue were used for the description of enzymatic activity of infected honey bees before treatment and 1, 2, 3, 5, 8 and 12 days after a one-time treatment with Nozevit. The possible effects of Nozevit treatment on the activity of the investigated enzymes and digestion are discussed.